Gold, Silver, and Palladium Nanoparticles: A Chemical Tool for Biomedical Applications - Yaqoob, Sundas Bahar; Adnan, Rohana; Rameez Khan, Raja Muhammad; Rashid, Mohammad (Frontiers in Chemistry, 2020)
Nanoparticles (NPs) play a crucial role in biomedical analysis and the treatment of critical deceases. In the world of nanotechnology, noble metals such as gold/silver/palladium (Au/Ag/Pd) NPs are the most emerging trend to design bioengineering materials which are to be employed as a modern diagnostic devices or drugs delivery technique to combat against many chronic disorders. NPs are considered as a powerful and advanced tool to diagnose and for the curing several diseases such as HIV, cancer, and other types of infectious diseases. The most significant application of nanotechnology is in the treatment of cancer cells which is based on premature tumor detection and analysis through several nano-devices accomplished of discerning levelling and delivery of drugs at the definite tumor site. The intriguing properties of NPs such as high surface area, high surface Plasmon resonance, multi-functionalization, highly stable nature, and easy processing makes them more prolific. In this review article, we focus on the role of Au/Ag/Pd NPs in the bio-medicinal field and physicochemical toxicity dependent properties along with the toxicity mechanism of NPs. The cytotoxicity effect of Au/Ag/Pd NPs and the future remarks are concluded to explore an idea for further research in the field of nanomaterials concern to bio-medicinal.